Broken (in the best possible way) ebook - Lawson, Jenny (2021)
An Instant New York Times Bestseller From the #1 New York Times bestselling author of Furiously Happy and Let 's Pretend This Never Happened comes a deeply relatable book filled with humor and honesty about depression and anxiety. As Jenny Lawson's hundreds of thousands of fans know, she suffers from depression. In Broken , Jenny brings readers along on her mental and physical health journey, offering heartbreaking and hilarious anecdotes along the way. With people experiencing anxiety and depression now more than ever, Jenny humanizes what we all face in an all-too-real way, reassuring us that we're not alone and making us laugh while doing it. From the business ideas that she wants to pitch to Shark Tan k to the reason why Jenny can never go back to the post office, Broken leaves nothing to the imagination in the most satisfying way. And of course, Jenny's long-suffering husband Victor—the Ricky to Jenny's Lucille Ball—is present throughout. A treat for Jenny Lawson's already existing fans, and destined to convert new ones, Broken is a beacon of hope and a wellspring of laughter when we all need it most. Includes Photographs and Illustrations